The struggle for the Bay : the life and times of Sandwip, an almost unknown Portuguese port in the Bay of Bengal in the sixteenth and seventeenth centuries - Mukherjee, Rila (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This article places Sandwip, a lesser known salt trading island and port in the Bay of Bengal within the nexus of global trade and politics in the seventeenth century. Sandwip is now a part of Bangladesh but at the time under review it was successively part of the medieval kingdoms of Bengal, Tripura and Arakan. Sandwip was, briefly, held by the Portuguese and is referred to in Portuguese annals as a ‘minor’ settlement, part of their ‘informal empire’ in the Bay. The article argues that we should not read such settlements of the Portuguese in Southasia as ‘formal’ or ‘informal’, ‘minor’ or ‘major’, and make thereby artificial distinctions between categories. We need to, instead, refocus and study Portuguese expansion as a multi pronged enterprise in which local exigencies and imperial vision were braided all over the Bay of Bengal.